Analysis of Profits for Vegetable Traders in the MMTC Market - Cut Aliyyah; Haifa Azalia Pinem; Vito Rogatina Nababan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the level of profit of retail vegetable business in the MMTC market in Medan City. The research method used is a quantitative method in the form of literature sources. Data collection techniques used are observation, interviews, and documentation. Marketing is the overall system of business activities aimed at planning, pricing, promoting, and distributing goods and services that can satisfy the needs of existing and potential buyers. 112 of 2007, the market is a meeting place for sellers who are able to sell goods/services, and a buyer who promises to buy an item at a certain price. Provisions for the occurrence of a market, namely: 1) there is a place of business, 2) there are goods and services Transactions, 3) some goods have sellers, 4) goods have buyers, 5) there is a relationship in buying and selling transactions.